Attenuation around the gallbladder on plain abdominal computed tomography as a predictor of surgical difficulty in laparoscopic cholecystectomy. Issue 4 (8th March 2021) - Iida, Hiroya; Maehira, Hiromitsu; Mori, Haruki; Kodama, Hirokazu; Tokuda, Aya; Takebayashi, Katsushi; Kojima, Masatsugu; Kaida, Sachiko; Miyake, Toru; Tani, Masaji
Abstract: Purpose: This study examined whether abdominal plain computed tomography (CT) can predict surgical difficulty in acute cholecystitis. Methods: We retrospectively analyzed 84 consecutive patients who underwent laparoscopic cholecystectomy for acute cholecystitis between January 2015 and December 2018. We distinguished three degrees of surgical difficulty based on the operative time and blood loss: difficult, both ≥120 minutes and ≥ 100 mL, respectively (n = 27); moderate, either ≥120 minutes or ≥ 100 mL, respectively (n = 30); and easy, both <120 minutes and < 100 mL, respectively (n = 27). We calculated the attenuation around the gallbladder on CT before surgery and compared the values among the three groups. Results: Mean age, albumin levels, C‐reactive protein levels, and the CT attenuation around the gallbladder ( P < .001) were significantly different between groups. The surgical difficulty was unrelated to the timing of surgery. The postoperative complications were more frequent in operations more than 72 hours after disease onset ( P = .04) and with CT attenuation around the gallbladder of ≥1.4 ( P = .036). Conclusion: High attenuation around the gallbladder on plain CT predicted a high surgical difficulty of laparoscopic cholecystectomy. We recommend measuring the CT attenuation around the gallbladder in patients with acute cholecystitis.